Multiple Myeloma-Derived Extracellular Vesicles Modulate the Bone Marrow Immune Microenvironment - Lopes, Raquel (2022)
Funding Information: This work was supported by Portuguese national funds, through FCT—Fundação para a Ciência e Tecnologia—in the context of the projects PDTC/MEC-HEM/30315/2017 and PCDC/MED-ONC/1215/2021, and by GILEAD GÉNESE (project PGG/058/2019). RL received a fellowship funded by FCT (2020.4875.BD). This work was also supported by the research infrastructure CONGENTO, co-financed by Lisboa Regional Operational Programme (Lisboa2020), under the PORTUGAL 2020 Partnership Agreement, through the European Regional Development Fund (ERDF) and FCT under the project LISBOA-01-0145-FEDER-022170. Fundings were not involved in the study design, collection, analysis, interpretation of data, writing of the article, or decision to submit it for publication.